Analysis of metallogenic material sources and metallogenic epoch of the Xiahulin lead-zinc deposit in inner Mongolia, China - Duan, Mingxin; Chen, Guihu; Liu, Tao; Liu, Liye; Zhao, Xidong (Frontiers in Earth Science, 2025)
The Xiahulin lead-zinc deposit serves as a classic skarn-type deposit in the Erguna Block of the Greater Khingan Range, containing uncertain metallogenic sources and epochs. The orebodies form complex shapes in the contact zone between granite and Sinian Ergunahe Formation rocks, with alteration zones characterized by skarnization and silicification, extending 1–5 m from the ore veins. The ores primarily comprise sphalerite, galena, chalcopyrite, pyrite, and quartz, with nested to disseminated structures. Mineralization occurs in four stages: pre-ore, early, main, and post-ore. Geochemical analyses revealed that the sphalerite in the main stage closely resembled syenogranite in trace elements. Sulfur isotopes (δ34SV-CDT = 3.46‰–5.96‰) indicated the magmatic sulfur origins, while led isotopes (208Pb/204 Pb = 38.188–38.214, 207Pb/204Pb = 15.591–15.599, 206Pb/204Pb = 18.437–18.442) suggested a mantle-crust mixed source. Zircon Hf isotopes (176Hf/177Hf = 0.282628–0.282846) and two-stage model ages (804–1309 Ma) indicated the partial melting of newly formed crustal material with minor contamination from ancient crust. The U-Pb dating of syenogranite zircons provided a diagenetic age of 203.8 ± 2.2 Ma. Based on geological and elemental evidence, Xiahulin mineralization likely occurred in the Early Jurassic, originating from the crust-mantle mixtures related to the Mongol-Okhotsk Ocean subduction, marking a period of notable mineralization in the Erguna Block.